Juvenile justice: a reference handbook - Shoemaker, Donald J. (Contemporary world issues. Criminal justice, 2016)
"Juvenile delinquency is a topic that has interested the public and academic scholars for decades. When hearing the word "delinquent," most people think of street gangs or bands of teens running loose and frightening people in streets or parks. However, delinquency covers a range of behaviors from minor offenses, such as trespassing, to the more serious crimes often associated with gangs"--